Numerical investigation of surface topography and residual stress after abrasive water jet sequential peening (AWJSP). Issue 4 (3rd July 2020) - He, Zhanshu; Zhao, Shusen; Li, Chao; Li, Dalei; Zhang, Yuanxi; Fu, Ting; Yu, Huixin
Abstract: This article reveals the formation mechanism of surface topography and the formation and coupling mechanism of residual stress field (RSF) after abrasive water jet sequential peening (AWJSP) that can sequential peening on the material surface at a certain distance interval, and proposes a mathematical model of surface dimple characteristic verified by simulation results. In addition, the influences of shot velocity v 0, shot radius R and the distance between the center of adjacent shots DC on surface topography and RSF were also investigated. Results show the surface dimple forms resulting from the material plastic strain, and the residual stress (RS) is mainly induced by the unrecovered elastic strain resulting from the hindering of plastic strain. Decreasing v 0, R or DC can decrease the surface roughness Rt, while increasing v 0 and R is beneficial to induce a large and deep compressive RS layer. DC influences the whole distribution of compressive RS layer directly.